Fluorescent glycoconjugates and their applications. (9th January 2020) - Thomas, Baptiste; Yan, Kai-Cheng; Hu, Xi-Le; Donnier-Maréchal, Marion; Chen, Guo-Rong; He, Xiao-Peng; Vidal, Sébastien
Abstract : Fluorescent glycoconjugates are discussed for their applications in biology in vitro, in cell assays and in animal models. Advantages and limitations are presented for each design using a fluorescent core conjugated with glycosides, or vice versa . Abstract : Glycoconjugates and their applications as lectin ligands in biology have been thoroughly investigated in the past decades. Meanwhile, the intrinsic properties of such multivalent molecules were limited essentially to their ability to bind to their receptors with high selectivity and/or avidity. The present review will focus on multivalent glycoconjugates displaying an additional capability such as fluorescence properties not only for applications toward imaging of cancer cells and detection of proteins or pathogens but also for drug delivery systems toward targeted cancer therapy. This review is a collection of research articles discussed in the context of the structural features of fluorescent glycoconjugates organized according to their fluorescent core scaffold and with their representative applications.